2021
DOI: 10.1177/21582440211022676
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Small-Scale Industries in a Local Geographic Space of Nigeria: An Assessment of the Impact of Strategic Interfirm Alliance

Abstract: The outbreak of Coronavirus pandemic has brought with it stagnation in all sectors of the economy, unemployment and loss of jobs, threats of recession, and annihilation of industries across the world. This paper examined the impact of strategic interfirm alliance on small-scale industries (SSI) amid the threat of COVID-19 pandemic in Nsukka, a local geographic space in Nigeria. A survey research design and a questionnaire survey of 82 SSIs were used in the paper. The data for the paper were analyzed using desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Nwokocha et al (2021) in their studies discovered that 24.81 percent, 25.01 percent, and 34.64 percent of the surveyed small scale industries saw relative increases, increases, and significant increases in their operations following the use of strategic alliance, while 5.06 percent and 10.48 percent had relative and significant decreases. Nwokocha and Madu (2021) also discovered that the need to accomplish "cost reduction, risk reduction, and resource accessibility" drives strategic alliance formation, rather than the spatial distribution of small and medium scale industries. Studies have also shown that strategic partnerships have a positive impact on the performance of the Nigerian telecommunication.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Similarly, Nwokocha et al (2021) in their studies discovered that 24.81 percent, 25.01 percent, and 34.64 percent of the surveyed small scale industries saw relative increases, increases, and significant increases in their operations following the use of strategic alliance, while 5.06 percent and 10.48 percent had relative and significant decreases. Nwokocha and Madu (2021) also discovered that the need to accomplish "cost reduction, risk reduction, and resource accessibility" drives strategic alliance formation, rather than the spatial distribution of small and medium scale industries. Studies have also shown that strategic partnerships have a positive impact on the performance of the Nigerian telecommunication.…”
Section: Literature Reviewmentioning
confidence: 88%